Fodder yield and nutritive value of subabul (Leucaena leucocephala Lam.) under diverse management regimes in coconut garden - Raj, Reshma M.; Raj, Asha K.; T. K., Kunhamu; V., Jammaludheen; Prakash, Anoob (Indian Journal of Agroforestry, 2020)
In spite of high protein deficits in ruminant nutrition, subabul, a potential fodder tree in tropical areas, is still under-utilized in Kerala owing to limited land availability for planting, low biomass yields and difficulty to harvest. The above problems can be solved by intercropping subabul as hedgerows in existing coconut gardens, but information on ideal management practices to maximize fodder yield and nutritive value is limited. Hence the present study was conducted to determine the optimum tree density and pruning frequency to maximise production of quality forage from subabul hedgerows underneath coconut garden, by comparing three levels of plant density viz. 49382, 37037 and 27777 plants ha-1 and three levels of pruning frequencies at 8, 12 and 16 weeks interval, laid out in 3 Ã— 3 factorial randomized block design, replicated thrice. The results indicated that plant density showed prominent influence on forage yield whereas fodder nutritive value was significantly influenced by pruning frequency. Annual fodder biomass and foliage fraction was greater from the highest density stand. Crude protein (CP) and ash content showed slight increment whereas, crude fibre (CF) content significantly decreased at higher densities indicating closer spacing for production of tender nutritive fodder. Harvesting at shortest interval of 8 weeks yielded maximum fodder, with the highest CP and least CF content compared to 12 and 16 weeks interval. However, ash content (8.70%) was significantly higher at the longest interval of 16 weeks. Thus the results conclude that in humid tropical conditions with annual rainfall of 210-300 cm, subabul should planted at the density of 49382 plants ha-1 in the interspaces of coconut and harvested at interval of 8 weeks to yield the maximum fresh and dry fodder (47.69 and 12.17 Mg ha-1yr-1) with superior quality, which offers a cheap source of quality forage to ruminants.